A Grounded Theory Analysis of Blended Learning as a Dual Stimulus for Critical Thinking and Self-Regulated Learning - Rima, Rosmania; Juniardi, Yudi; Syafrizal, Syafrizal (PPSDP International Journal of Education, 2025)
This qualitative case study explores the intricate relationship between self-regulated learning (SRL) and critical thinking in a blended learning environment. Using a case study approach, the research aims to develop a substantive theory that explains the pedagogical mechanisms underlying the effectiveness of this modality. Data was collected from 34 participants through a 55-item SRL questionnaire, student interviews, and document analysis of critical thinking test results based on Ennis’s indicators. The study followed the core procedures of grounded theory, including open, axial, and selective coding. The findings led to the development of the Integrated Critical Stimulation conjecture, which posits that blended learning is a uniquely synergistic approach that effectively fosters critical thinking. This synergy is a “dual stimulus,” where the face-to-face component provides crucial scaffolding and real-time feedback, and the online component offers a space for autonomous practice and deep reflection. The study’s most significant finding is that this synergy is particularly effective for students with moderate SRL abilities, who benefit from the balanced support and autonomy the blended model provides. The conjecture suggests that a deliberate and strategic integration of modalities, tailored to student characteristics, is key to developing critical thinking skills.